O Reggae no Maranhão: música, mídia, poder - Brasil, Marcus Ramúsyo de Almeida (2011)
The political dimension that surrounds the relations between music, popular culture and media productions is the main theme of the present study. The focus of the empirical observation performed was on the ties that connect media and marketing power to institutional politics. For such, the reggae phenomenon was analyzed from its genesis to nowadays, specially its path in the state of Maranhão and its capital, São Luís, from 1970 to 2011, with attention to the relations of its growth and broadcasting through radio and television programs, sound systems circuits, reggae club parties and the institutional political system. The main purpose was to analyze the relations between artistic expression, media and politics inside reggae in Jamaica and Maranhão; to understand how and why reggae possesses such a mobilizing potential and significant power to affect subjectivities, having established itself as a cultural element in Maranhão. The methodology was based upon a historical approach, and field procedures centered in direct observation, video and photographic documentation allied with the analysis of songs, videos, media and marketing materials. The theory references are set amongst authors that collaborate with reggae s historicity and with discussions in the areas of sociology of culture and cultural studies, such as White (1999), Albuquerque (1997), Silva (2007, 1992), Williams (2008, 1997), Benjamin (1994), Sodré (2006, 1998), Martín-Barbero (2001, 2004), Hall (2003), and others. The analysis sustained the initial theses that the reggae movement, as its symbolical apparatus, are being used and transformed by local politicians, through political marketing and media instrumentation strategies, into potential political influence and power